MEASURING HEAD NURSES’ COACHING PRACTICE: MODIFYING AND TESTING THE INSTRUMENT FOR ASSESSING MANAGERIAL COACHING SKILLS - Romiko, .; Jumpamool, Apinya (LIFE: International Journal of Health and Life-Sciences, 2016)
Managerial coaching has been reported as a successful leadership development approach that has potential benefit for nurses. It also was recognized as a powerful tool to promote personal and professional development in the nursing profession. Therefore, there is an increasing needs for reliable and valid assessment tools to measure the coaching skills of nurses in managerial positions. This study reviewed and revised an existing instrument created by (Park, McLean, and Yang, 2007) which measured coaching skills of managers in business and industrial organization. In order to adapt the original instrument to the nursing profession, this study firstly identified the five primary dimensions of the managerial coaching skills of head nurses through both qualitative and quantitative approaches. Review experts and a pilot study were then performed to ensure the reliability and validity, and validated the revised instrument of managerial coaching skills. The results of this study indicate the revised managerial caching skill instrument demonstrates good reliability and validity for measuring the managerial coaching skill of head nurses in a hospital setting. Hospitals can administer and use the revised instrument as an assessment tool to evaluate their nurse managers’ coaching skills, and identify the areas for improvement. This allow the head nurses to more effectively manage and support the staffs’ development.